Expansion and preservation of multipotentiality of rabbit bone-marrow derived mesenchymal stem cells in dextran-based microcarrier spin culture - Boo, Lily; Selvaratnam, Lakshmi; Cheh, Chin Tai; Ahmad, Tunku Sara; Kamarul, Tunku (Springer Verlag, 2011)
The use of mesenchymal stem cells (MSCs) in tissue repair and regeneration despite their multipotentiality has been limited by their cell source quantity and decelerating proliferative yield efficiency. A study was thus undertaken to determine the feasibility of using microcarrier beads in spinner flask cultures for MSCs expansion and compared to that of conventional monolayer cultures and static microcarrier cultures. Isolation and characterization of bone marrow derived MSCs were conducted from six adult New Zealand white rabbits. Analysis of cell morphology on microcarriers and culture plates at different time points (D0, D3, D10, D14) during cell culture were performed using scanning electron microscopy and bright field microscopy. Cell proliferation rates and cell number were measured over a period of 14 days, respectively followed by post-expansion characterization. MTT proliferation assay demonstrated a 3.20 fold increase in cell proliferation rates in MSCs cultured on microcarriers in spinner flask as compared to monolayer cultures (p < 0.05). Cell counts at day 14 were higher in those seeded on stirred microcarrier cultures (6.24 ± 0.0420 cells/ml) × 10(5) as compared to monolayer cultures (0.22 ± 0.004 cells/ml) × 10(5) and static microcarrier cultures (0.20 ± 0.002 cells/ml) × 10(5). Scanning electron microscopy demonstrated an increase in cell colonization of the cells on the microcarriers in stirred cultures. Bead-expanded MSCs were successfully differentiated into osteogenic and chondrogenic lineages. This system offers an improved and efficient alternative for culturing MSCs with preservation to their phenotype and multipotentiality.